"y'(x)=\\sum_{n=1}^\\infin na_nx^{n-1}""y''(x)=\\sum_{n=2}^\\infin n(n-1)a_nx^{n-2}"
"x^2\\sum_{n=2}^\\infin n(n-1)a_nx^{n-2}+(4x-x^2)\\sum_{n=1}^\\infin na_nx^{n-1}+(2-x)\\sum_{n=0}^\\infin a_nx^n=0"
"\\sum_{n=2}^\\infin n(n-1)a_nx^{n}+\\sum_{n=1}^\\infin 4na_nx^{n}-\\sum_{n=1}^\\infin na_nx^{n+1}+\\sum_{n=0}^\\infin 2a_nx^n-\\sum_{n=0}^\\infin a_nx^{n+1}=0"
"\\sum_{n=2}^\\infin n(n-1)a_nx^{n}+\\sum_{n=1}^\\infin 4na_nx^{n}-\\sum_{n=2}^\\infin (n-1)a_{n-1}x^{n}+\\sum_{n=0}^\\infin 2a_nx^n-\\sum_{n=1}^\\infin a_{n-1}x^{n}=0"
"2a_0+\\sum_{n=1}^\\infin [n(n-1)a_n+4na_n- (n-1)a_{n-1}+ 2a_n- a_{n-1}]x^{n}=0"
"n=0 ; a_0=0"
"a_n=na_{n-1}\/[n(n-1)+4n+2]"
"y(x)=0"
Comments
Leave a comment